Lipid mobilization in subcutaneous adipose tissue during exercise in lean and obese humans. Roles of insulin and natriuretic peptides - Koppo, Katrien; Larrouy, Dominique; Marques, Marie A; Berlan, Michel; Bajzova, Magda; Polak, Jan; Van de Voorde, Johan; Bülow, Jens; Lafontan, Max; Crampes, François; Langin, Dominique; Stich, Vladimir; et al. (American journal of physiology. Endocrinology and metabolism, 2010)
The aim of this study was to evaluate the relative contributions of various hormones involved in the regulation of lipid mobilization in subcutaneous adipose tissue (SCAT) during exercise and to assess the impact of obesity on this regulation. Eight lean and eight obese men performed a 60-min cycle exercise bout at 50% of their peak oxygen uptake on two occasions: during intravenous infusion of octreotide (a somatostatin analog) or physiological saline (control condition). Lipolysis in SCAT was evaluated using in situ microdialysis. One microdialysis probe was perfused with the adrenergic blockers phentolamine and propranolol while another probe was perfused with the phosphodiesterase and adenosine receptor inhibitor aminophylline. Compared with the control condition, infusion of octreotide reduced plasma insulin levels in lean (from approximately 3.5 to 0.5 microU/ml) and in obese (from approximately 9 to 2 microU/ml), blunted the exercise-induced rise in plasma GH and epinephrine levels in both groups, and enhanced the exercise-induced natriuretic peptide (NP) levels in lean but not in obese subjects. In both groups, octreotide infusion resulted in higher exercise-induced increases in dialysate glycerol concentrations in the phentolamine-containing probe while no difference in lipolytic response was found in the aminophylline-containing probe. The results suggest that insulin antilipolytic action plays a role in the regulation of lipolysis during exercise in lean as well as in obese subjects. The octreotide-induced enhancement of exercise lipolysis in lean subjects was associated with an increased exercise-induced plasma NP response. Adenosine may contribute to the inhibition of basal lipolysis in both subject groups.
Keywords: obezita; zátěžový test; metabolismus lipidů; tuková tkáň; anaerobní práh; Glycerol; Rest; Humans; glycerol; Anaerobic Threshold; Lipid Metabolism; natriuretické peptidy; mladý dospělý; dospělí; Adrenergic alpha-2 Receptor Agonists; Natriuretic Peptides; katecholaminy; cyklické nukleotidfosfodiesterasy, typ 3; beta blokátory; lidé; oktreotid; Exercise Test; Octreotide; Aminophylline; Adult; Phosphodiesterase Inhibitors; Male; Insulin; alfa-2-adrenergní receptory - agonisté; inhibitory fosfodiesteras; odpočinek; Young Adult; Catecholamines; Obesity; Exercise; Cyclic Nucleotide Phosphodiesterases, Type 3; mužské pohlaví; cvičení; Adrenergic beta-Antagonists; aminofylin; Adipose Tissue; agonisté adrenergních alfa-receptorů; Adrenergic alpha-Agonists; inzulin